Mortalidade por homicídios no Paraná : análise da tendência e perfil epidemiológico - Lozada, Elizabeth Mitiko Konno de (2008)
The objectives of this study were to analyze the trends and profile in the mortality rate by homicides in the state of Paraná during the period from 1979 to 2005, and to identify the characteristics of the persons killed according to gender, age, type of lesion, place of residence, race/ethnicity and education level. It is an exploratory descriptive study, of the ecological type. The studied population was composed of all homicide deaths of residents in the state of Paraná, in the period from 1979 to 2005. The mortality data were obtained starting from tabulations of the Mortality Information System (SIM) of the Ministry of Health. This study also tallied to homicide numbers all deaths resulting from legal interventions, firearm deaths of uncertain intention and cold steel deaths of uncertain intention. The data were analyzed through ratios and mortality coefficients. For the ratios, the data were divided into five periods - 1979 to 1985, 1986 to 1991, 1992 to 1996, 1997 to 2000 and 2001 to 2005. The coefficients were divided into six three-year periods - 1979-1981, 1984-1986, 1990-1992, 1995- 1997, 1999-2002 and 2003-2005. The analysis of homicide mortality trends was accomplished applying moving average and analysis of the annual variation of the coefficients. At the start of the studied period, homicides occupied the fourth position among the main external causes of death, with 15.5%; in 1997 they took second place, with 22.4%; and in 2005, deaths from homicide already represented close to 35.5% of deaths, comparable to deaths from transportation accidents (36.3%), which were the main cause. The male-to-female death ratio was 10:1 during almost the entire studied period. The homicide mortality behavior for males increased, from 26.1 deaths per 100,000 inhabitants in the 1979-1981 three-year period, to 47.1 in the three-year period from 2003 to 2005; it remained stable for females. The 15-to-49- year-old age group comprised over 80% of total deaths in the 26 studied years. In the three-year period between 2003 and 2005, the largest mortality coefficients were verified in the age groups from 20 to 29 years of age (59.8 deaths per 100,000 inhabitants) and from 15 to 19 years of age (50.1 per 100,000 inhabitants). For 2003 2005, the study obtained a coefficient of 110.8 per 100,000 inhabitants for males and 8.2 per 100,000 inhabitants for females, in the age group from 20 to 29 years of age. As for the type of aggression, firearms were the most frequent during the studied period, particularly in the period from 2001 to 2005, when they were responsible for 67.8% of aggressions; followed by cold steel, with 18% of the total. In the three-year period from 2003 to 2005, the largest mortality coefficients were verified in men from 15 to 49 years of age, at the Metropolitan, Londrina and Foz do Iguaçu health sectionals - 110.9 per 100.000 inhabitants, 98.7 per 100,000 inhabitants and 224.0 per 100,000 inhabitants, respectively. The largest positive annual percentage variation of the mortality coefficient for homicides in males from 15 to 49 years of age was observed in the health sectionals of Campo Mourão with 26.9%, Cianorte with 25.4%, and Londrina with 24.9%. As for homicide mortality in males from 15 to 49 years of age, according to race/ethnicity, the prevalence of the deaths is for Caucasian race/ethnicity, with 79.8% of total deaths in Paraná during the three-year period from 2003-2005. According to education, 78.3% of homicide victims had less than 7 years of formal education for the three-year period between 2003 and 2005.The analysis of mortality trend of homicides has shown that the deaths homicides are increasing in Parana, especially in young men. These results help to broaden the knowledge of the epidemiological aspects of deaths by homicide and reinforce the need for action articulated in various sectors and segments of society.